Nuciferine Ameliorates Inflammatory Responses by Inhibiting the TLR4-Mediated Pathway in Lipopolysaccharide-Induced Acute Lung Injury - Wu, Haichong; Yang, Yaping; Guo, Shuai; Yang, Jing; Jiang, Kangfeng; Zhao, Gan; Qiu, Changwei; Deng, Ganzhen (Frontiers in Pharmacology, 2017)
Acute lung injury (ALI) is a complex syndrome with sepsis occurring in critical patients, who usually lack effective therapy. Nuciferine is a primary bioactive component extracted from the lotus leaf, and it displays extensive pharmacological functions, including anti-cancer, anti-inflammatory, and antioxidant properties. Nevertheless, the effects of nuciferine on lipopolysaccharide (LPS)-stimulated ALI in mice has not been investigated. ALI of mice stimulated by LPS was used to determine the anti-inflammatory function of nuciferine. The molecular mechanism of nuciferine was performed on RAW264.7 macrophage cells. The results of pathological section, myeloperoxidase activity and lung wet/dry ratio showed that nuciferine alleviated LPS-induced lung injury (p<0.05). qRT-PCR and ELISA experiments suggested that nuciferine inhibited TNF-α, IL-6 and IL-1β secretion in tissues and RAW264.7 cells but increased IL-10 secretion (p<0.05). Molecular studies showed that TLR4 expression and nuclear factor (NF)-κB activation were both inhibited by nuciferine treatment (p<0.05). To further investigate the anti-inflammatory mechanism of nuciferine, TLR4 was knocked down. When TLR4 was silenced, LPS induced the production of IL-1β,and TNF-α was markedly decreased by TLR4-siRNA and nuciferine treatment in LPS-induced RAW264.7 cells (p<0.05). These results suggested that nuciferine had the ability to protect against LPS-stimulated ALI. Thus, nuciferine may be a potential drug for treating LPS-induced pulmonary inflammation.